Acute appendicitis with leukemic infiltration in a child with acute myeloid leukemia: A case report - Ana Laura Moraes Luzardi; Felippe Flausino; Imaruí Costa; Luiza Maes Manara; Maria Alice Correa Accetturi; Suani da Costa Santos; Carolina Petersen Moojen; Lívia Volta Bernardes Dias (Elsevier, 2023)
Introduction: Leukemic infiltration of the appendix is extremely rare, especially when it presents with a clinical picture similar to acute appendicitis. We describe the case of a 7-year-old child, recently diagnosed with acute myeloid leukemia (AML), who developed symptoms and signs of acute appendicitis. Histology results demonstrated leukemic infiltration of the appendix. Case presentation: A previously healthy 7-year-old-male child presented with a 10-day history of fever, body aches and diffuse abdominal pain. Laboratory tests showed a significant leukocytosis with 90 % of blasts. Bone marrow aspirate was compatible with AML. On the fourth day of hospital stay, he presented with severe abdominal pain, abdominal distension and diarrhea. Abdominal computerized tomography (CT) showed a long appendix, with marked parietal thickening in its distal third. The patient underwent a standard laparoscopic appendectomy. Histology evaluation revealed infiltration by acute myeloid leukemia. Conclusion: Our report describes an accurate diagnosis and surgical treatment of an acute appendicitis with leukemic infiltration in an infant with AML. Despite its rarity, surgeons need to be aware of this condition as a differential diagnosis of a surgical acute abdomen in children with leukemia. We suggest doing an appendectomy in children with leukemia and a thickened appendix, if they have symptoms of acute appendicitis, to determine if it is true appendicitis or leukemic infiltration.